Modeling from the first principles of the electronic properties of compositions of REE as precursors of high-temperature superconductors - A. V. Gulay; A. V. Dubovik (Системный анализ и прикладная информатика)
Modeling of the first principles of the electronic properties of complex oxides of rare earth elements (BaY2O4, BaGd2O4, BaLu2O4) as precursors of high-temperature superconductors has been performed. The VASP software package was used as a modeling environment, in particular the method of coupled plane waves (PAW method), which allows us to obtain fairly accurate results for calculating the electron density and band structure. From the analysis of the obtained band energy structure, it follows that the studied REE oxides have a band gap width Eg = 3.29–3.84 eV, which is characteristic for dielectric materials. The studied compounds based on these rare earth elements selected from the yttrium (Y, La, Gd–Lu) and cerium (Ce–Eu) groups are characterized by an increase in Fermi energy and a decrease in the band gap as the atomic number (39, 64, 71) of the element in the periodic table increases. A method for modeling the quantum layers of the studied materials by simulating the restriction of the crystal structure along one of the coordinate axes is proposed. This representation approximates the model of the crystal lattice of REE oxides to the situation of analyzing a quantum layer whose thickness is equal to the size of the crystal cell along the specified axis. The rupture of atomic bonds in a crystal is simulated by increasing the distance between atomic layers along this axis to values at which the value of free energy is stabilized. In the quantum layer of rare earth element oxide (with its thickness close to 1 nm), a wider range of energy values is formed in which electrons are distributed than is observed in the continuous version, and the expansion of the electron distribution area extends to the energy levels of the band gap. This is explained by the fact that the geometric discretization of nanoscale structures determines the discreteness of the quantum-dimensional energy spectrum.